Influência de indicadores socioeconômicos e ambientais sobre as infrações ambientais nos municípios do Centro Técnico Regional de Fiscalização de Sorocaba - Tremeschini, Letícia Horvath (Universidade Federal de São Carlos, 2016)
In face of the worldwide need for preservation of the environment, specific legislations have been developed aiming to assure the environmental rights and allow their attackers to be punished. It is however needs to understand the dynamics of the sanctions that are applied and their relations with the socioeconomic and environmental indicators of the counties where they written the infractions records. It is expected, therefore, to contribute with the formulation and execution of public policies for the preservation and conservation of the environment. In this sense, have been evaluated the influence of some socioeconomics and environmental indicators in the number of infractions records issued in the municipalities that are located in Sorocaba Inspection Regional Technical Center. The indicators used were: area, population, per capita income, municipal gross domestic product, municipal human development index, basic education development index, native forest, the distance from environmental military police headquarters, and also the location of dams and large rivers. The categories of environmental infractions were grouped empirically, and the municipalities by the multivariate method called cluster analysis and the influences of the indicators about the infractions were obtained by multiple regression method. During the considered period, the largest number of infractions have been written in the category "common area", and the year of 2011 which were written the largest number of records. As the analyzed counties, Ibiuna has presented as the place where the majority of the written infractions occurred. Statistically significant relations were found between the number of infractions with the indicators: population, municipal gross domestic product, native forest and the distance from environmental military police headquarters. In general, some adjustments have not resulted in satisfactory statistical models, in which the variables little explain the number of infractions. Even for the adjustments with statistical significance and high values of the coefficients, it was not possible to find scientific explanation or empirical evidence conclusive to justify the relation. Both results indicate that other variables, that not those used in this study, influence the relations analyzed. For this reason, it is necessary that additional studies are performed to help the formulation and implementation of environmental policies.
Influence of Environmental and Socioeconomic Indicators about the Environmental Infractions on the Counties of Sorocaba Inspection Regional Technical Center, SP
Keywords: Política ambiental; Environmental policy; Direito ambiental; Environmental law; Responsabilidade por danos ambientais; Liability for environmental damages; Infração administrativa; Fiscalização ambiental; Administrative Infraction; Environmental Inspection; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA